PENGARUH MODEL PEMBELAJARAN STEAM TERHADAP HASIL BELAJAR IPA PESERTA DIDIK KELAS V SEKOLAH DASAR KELURAHAN KEMAYORAN JAKARTA PUSAT - Sirait, Eunike; Sekaringtyas, Tunjungsari; Angger Wardhani, Prayuningtyas (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine whether or not the STEAM learning model has an effect on the science learning outcomes of fifth-grade elementary school students. This study is a quantitative study using an experimental method with a pretest-posttest control group design. The study population includes all fifth-grade elementary school students in the Kemayoran sub-district of Central Jakarta. The study sample was obtained through cluster random sampling using a lottery method. Based on the lottery results, SDN Kemayoran 11 class V-A was designated as the experimental class and class V-B as the control class. The prerequisite data analysis tests included a normality test using the Liliefors test and a homogeneity test using the Bartlett test. Hypothesis testing was performed with a t-test at a significance level of α = 0.05. The calculation results showed that the t_count (12.268) > t_table (1.677), so H_0 was rejected and H_1 was accepted. Thus, the results showed that there was a positive and significant effect of the STEAM learning model on the science learning outcomes of fifth-grade elementary school students. Therefore, the STEAM learning model can be used as an alternative learning model in science lessons so that learning objectives can be achieved optimally and have a positive impact on student learning outcomes.